Example of Implementation of the Human Attitude of the Head of Police and WH Syabri S.Pd and Partners to Turn Challenges Into Opportunities in the Millenial Age of Students of SMA Negeri 1 Blangkejeren - Yusuf Hanafi Pasaribu; Yulkarnaini Siregar; July Esther; Dewi Robiyanti; Syabri Syabri (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The operational implementation of Public Order and Order (Trantibum) carried out by the Regency/Municipal Civil Service Police Unit (Satpol PP) in Blangkejeren must be based on a humane and authoritative attitude. To improve the image, Satpol PP must have a sense of humanity and authority in carrying out their duties. "So with this attitude, the image of Satpol PP can improve and be better. It's not like what people say that Satpol is the enemy of the small people, has a bad image, and is a tool for ruling over the little people. Thus, the community will be able to understand by creating a high sense of awareness regarding the attitudes and actions they take. From their observations regarding the actions taken by the district/city Satpol PP when carrying out control in their area, it has referred to the regulations that have been set by the Minister of Home Affairs No. 26/2005 concerning Procedural Guidelines. Still Operational Satpol PP.” Where in the regulation has been stipulated related to the implementation of the Trantibum, raids. Before the Satpol PP carries out the operation, socialization will be carried out first, so that when the operation is carried out there is no anarchic attitude.